The archaeology of Britain
1 online resource
Keywords: "The Archaeology of Britain is the only concise and up-to-date introduction to the archaeological record of Britain from the reoccupation of the landmass by Homo sapiens during the later stages of the most recent Ice Age until last century. This fully revised third edition extends its coverage, and includes updates relating to the latest research and advances in scientific dating and other techniques. This includes the results of the latest analyses of ancient DNA, alongside new isotopic studies which enable insights into ancient diets. The chapters are written by experts in their respective fields. Each is geared to provide an authoritative but accessible introduction, supported by numerous illustrations of key sites and finds and a selective reference list to aid study in greater depth. It provides a one-stop textbook for the entire archaeology of Britain and reflects the most recent developments in archaeology both as a field subject and as an academic discipline. No other book provides such comprehensive coverage, with such a wide chronological range, of the archaeology of Britain. This collection is essential reading for undergraduates in archaeology, and all those interested in British archaeology, history and geography"-- Provided by publisher.